Nano-springe enriched hierarchical porous MOP/COF hybrid aerogel: efficient recovery of gold from electronic waste - Majumder, Dipanjan; Fajal, Sahel; Shirolkar, Mandar M.; Torris, Arun; Banyla, Yashasvi; Biswas, Kishalay; Rasaily, Sagarmani; Ghosh, Sujit K. (Angewandte Chemie-International Edition, 2025)
Extraction of gold from secondary resources such as electronic waste (e-waste) has become crucial in recent times to compensate for the gradual scarcity of the noble metal in natural mines. However, designing and synthesizing a suitable material for highly efficient gold recovery is still a great challenge. Herein, we have strategically designed rapid fabrication of an ionic crystalline hybrid aerogel by covalent threading of an amino-functionalized metal-organic polyhedra with an imine-linked chemically stable covalent organic framework at ambient condition. The hierarchically porous ultra-light aerogel featuring imine-rich backbone, high surface area, and cationic sites have shown fast removal, high uptake capacity (2349 mg/g), and excellent selectivity towards gold sequestration. Besides, the aerogel can extract ultra-trace gold-ions from different terrestrial water bodies, aiming towards safe drinking water. This study demonstrates the great potential of the composite materials based on a novel approach to designing a hybrid porous material for efficient gold recovery from complex water matrices.
Keywords: Aerogel; COF; E-waste; Gold; MOP